Ascending central canal dilation and progressive ependymal disruption in a contusion model of rodent chronic spinal cord injury - Radojicic, Milan (BioMed Central, 2007)
BACKGROUND: Chronic spinal cord injury (SCI) can lead to an insidious decline in motor and sensory function in individuals even years after the initial injury and is accompanied by a slow and progressive cytoarchitectural destruction. At present, no pathological mechanisms satisfactorily explain the ongoing degeneration. METHODS: Adult female Sprague-Dawley rats were anesthetized laminectomized at T10 and received spinal cord contusion injuries with a force of 250 kilodynes using an Infinite Horizon Impactor. Animals were randomly distributed into 5 groups and killed 1 (n = 4), 28 (n = 4), 120 (n = 4), 450 (n = 5), or 540 (n = 5) days after injury. Morphometric and immunohistochemical studies were then performed on 1 mm block sections, 6 mm cranial and 6 mm caudal to the lesion epicenter. The SPSS 11.5 t test was used to determine differences between quantitative measures. RESULTS: Here, we document the first report of an ascending central canal dilation and progressive ependymal disruption cranial to the epicenter of injury in a contusion model of chronic SCI, which was characterized by extensive dural fibrosis and intraparenchymal cystic cavitation. Expansion of the central canal lumen beyond a critical diameter corresponded with ependymal cell ciliary loss, an empirically predictable thinning of the ependymal region, and a decrease in cell proliferation in the ependymal region. Large, aneurysmal dilations of the central canal were accompanied by disruptions in the ependymal layer, periependymal edema and gliosis, and destruction of the adjacent neuropil. CONCLUSION: Cells of the ependymal region play an important role in CSF homeostasis, cellular signaling and wound repair in the spinal cord. The possible effects of this ascending pathology on ependymal function are discussed. Our studies suggest central canal dilation and ependymal region disruption as steps in the pathogenesis of chronic SCI, identify central canal dilation as a marker of chronic SCI and provide novel targets for therapeutic intervention.